Exploring undergraduate students' experiences with technology in online learning environment - Kusmiatun, Ari; Ardhia, Dhiana Nur; Kencana, Bekti Anggi Kuala (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
As an aftermath of the COVID-19 pandemic, university learning has been significantly impacted despite the need to adapt to technology to support online learning. Nonetheless, it is essential to recognize that online learning can pose various challenges, including learning loss, which can affect the decline of students' knowledge and skills. The present study was aimed at identifying (1) the types of platforms used in online learning and (2) the symptoms of learning loss experienced by students during online learning. The study was quantitative-qualitative research with a mix-method approach. Data collection was carried out using observations, online surveys (Google form), and interviews conducted in 2021. Data were collected from 70 students of Indonesian Language and Literature Education class of 2020 Yogyakarta State University. Data analysis used quantitative-qualitative analysis. The results showed that the types of platforms students use include WhatsApp, Zoom, UNY Be Smart, Google Meet, Google Classroom, Powtoon, Geneally, Padlet, Quiziz, and Jamboard. The Whatsapp was the most widely used platform. However, online learning that provides many benefits also caused symptoms of learning loss in online lectures. The symptoms of learning loss experienced by students were lecturing while doing other activities, no one responding to the lecturer's questions, turning off the camera during lectures, and passive discussion presentations. The findings suggest that lecturers should increase their supervision and engagement, create a more engaging learning environment, and encourage active participation from students.